2008
DOI: 10.1080/13682820701608001
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap: can impairment‐based therapy for anomia have an impact at the psycho‐social level?

Abstract: The findings suggest that therapy which targets word retrieval can have an impact on people with aphasia's views of their communicative activity and life participation. The findings support therapists' clinical insight that impairment-based interventions can effect change beyond scores on language tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 25 publications
0
20
0
1
Order By: Relevance
“…While it may be that this was as a direct result of improved naming, it may also have been due to increased confidence in the participants. Best et al (2008) found that following naming therapy participants rated that they had greater participation in situations that required communication. Best et al suggested that participation in naming therapy impacted on the views that the participants' held about their own communication.…”
Section: Discussion Part 2: Word Retrieval In Conversationmentioning
confidence: 99%
See 1 more Smart Citation
“…While it may be that this was as a direct result of improved naming, it may also have been due to increased confidence in the participants. Best et al (2008) found that following naming therapy participants rated that they had greater participation in situations that required communication. Best et al suggested that participation in naming therapy impacted on the views that the participants' held about their own communication.…”
Section: Discussion Part 2: Word Retrieval In Conversationmentioning
confidence: 99%
“…The aim of such an approach is to improve underlying speech and/or language impairments so as to reduce the disability and improve the functioning of the person with aphasia; in other words, to benefit communication in everyday life (Best, Greenwood, Grassly, & Hickin, 2008). As such, the aim is that any improvements in word retrieval that occur at the single word level would also be reflected in improvements at the level of conversation.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…In other words, the elusive finding of generalized improvement in word retrieval skills, for example, as indicated by greater accuracy scores on treated and untreated sets of target words, has been the exception rather than the rule in published studies. 26 This has led to several studies in which the primary goal has been improved reliability of production for purposefully trained items, for example, usually vocabulary items, which are agreed to be communicatively relevant to an individual participant, 5,[27][28][29] where generalized improvement in word retrieval skills was taken to be a possible but not a probable therapy outcome. Such studies have negotiated target words for training on the basis of likely everyday use in conversation or general interaction; proper names of family members and friends are one example.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding specific therapy approaches and interventions to improve QoL and HRQL, there is promising evidence for group therapy in terms of psychosocial benefits [31,32] and improved social participation and social connection compared with controls [33]; for impairment-based therapy for word-finding difficulties, when targeted around an individual's interests [34]; for intensive comprehensive aphasia programs [35], as well as for models of community service provision [36,37,38,39]. Yet, further research in these areas with larger sample sizes and appropriate control groups will increase our confidence in these findings.…”
Section: Qol In Aphasia: Where Next?mentioning
confidence: 99%